Shared executive dysfunctions in unaffected relatives of patients with autism and obsessive-compulsive disorder - Delorme, Richard (Editions scientifiques Elsevier, 2007)
BACKGROUND: Executive dysfunctions have been studied as a potential endophenotype associated with the genetic basis of autism. Given that recent findings from clinical and molecular genetic studies suggest that autism and obsessive-compulsive disorder (OCD) could share a common pattern of heritability, we assessed executive functions as a possible common cognitive endophenotype in unaffected family members of individuals with either autism or OCD. METHODS: Five tests assessing executive functions (Tower of London, verbal fluency, design fluency, trail making and association fluency) were proposed to 58 unaffected first-degree relatives (parents and siblings) of probands with autism and 64 unaffected first-degree relatives of OCD patients. Results were compared with those of 47 healthy controls matched for age, sex, and level of education. RESULTS: In the Tower of London test, both groups of unaffected relatives showed significantly lower scores and longer response times compared with controls. No differences were observed between autism and OCD relatives and healthy controls in the four other tasks (verbal fluency, design fluency, trail making test and association fluency). CONCLUSIONS: Our findings show the existence of executive dysfunction in the unaffected first-degree relatives of probands with OCD, similar to those observed in the relatives of patients with autism. These results support and extend previous cognitive studies on probands indicating executive dysfunctions in autism and OCD. Planning and working memory processes could thus represent a common cognitive endophenotype in autism and OCD that could help in the identification of genes conferring vulnerability to these disorders.